Plantationo(s)cenes: Creative Activism and Sri Lankan Plantation Workers - Yasmin Gunaratnam; Menaha Kandasamy (Social Sciences)
This paper describes the methods of creative activism used by a women-led plantation trade union in Sri Lanka to improve workers’ living and working conditions. We discuss how the feminist idea of “relational humility” is a vital component of how creative activism with plantation workers can work against extractive forms of research and knowledge-making. The paper unfolds in three parts. After setting out our orienting ideas and describing the colonial history of Sri Lankan plantations, we present two examples of unexpected relational humility, first in a workshop and then in a plantation Sunday School. Finally, we suggest the particular value of trade union research in taking up and locating research findings within workers’ self-organised struggles for sustainable living and working conditions.